2016
DOI: 10.1002/anie.201601445
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Complexes of Germanone from a Germanium μ‐Oxo Dimer

Abstract: Complexes of germanone containing formal Ge=O→M bonds (M=Zn, B, Ge, Sn) were isolated and characterized. The compounds were prepared through a novel synthetic route using a germanium μ-oxo dimer 3 as the starting material. This method circumvents the need to employ germanones to prepare complexes of germanones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The Ge-S bond distances ( 6a : 2.2462(13) Å and 2.2406(13) Å, 6b : 2.231(3) Å and 2.237(3) Å) are in the range reported of Ge-S single bonds (2.17–2.25 Å) [61], and longer than the Ge=S double bond length of 2.049(3) Å in [Tbt(Trip)Ge=S] (Tbt = 2,4,6-{(Me 3 Si) 2 CH} 3 C 6 H 2 , Trip = 2,4,6- i Pr 3 C 6 H 2 ) [62]. To investigate the reaction mechanism, we attempted to quench the reaction intermediate employing Lewis bases (pyridine, Me 3 N, Ph 3 P and Et 3 N) and Lewis acids (BPh 3 and B(C 6 F 5 ) 3 ) [63,64,65]. However, none of them afforded any trapped products, and only the formation of 6a and 6b were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The Ge-S bond distances ( 6a : 2.2462(13) Å and 2.2406(13) Å, 6b : 2.231(3) Å and 2.237(3) Å) are in the range reported of Ge-S single bonds (2.17–2.25 Å) [61], and longer than the Ge=S double bond length of 2.049(3) Å in [Tbt(Trip)Ge=S] (Tbt = 2,4,6-{(Me 3 Si) 2 CH} 3 C 6 H 2 , Trip = 2,4,6- i Pr 3 C 6 H 2 ) [62]. To investigate the reaction mechanism, we attempted to quench the reaction intermediate employing Lewis bases (pyridine, Me 3 N, Ph 3 P and Et 3 N) and Lewis acids (BPh 3 and B(C 6 F 5 ) 3 ) [63,64,65]. However, none of them afforded any trapped products, and only the formation of 6a and 6b were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it has been demonstrated that ATI ligands are well‐suited for stabilizing heavy analogs of carbon oxo compounds. With the Ge IV complexes [GeO(ATI i Bu/ i Bu ) i Pr(LA)] ( 45‐LA ) were the first Lewis acid adducts of a heavy ketone analog isolated and fully characterized (Scheme a; LA = Lewis acid) . DFT calculations confirmed a decreased ATI Ge–O bond order for 45‐LA [Wiberg bond indices (WBI): 0.60–0.72] compared to that in the theoretically investigated parent germanone 45 (WBI: 1.08).…”
Section: Heavy Analogs Of Carbon Oxo Compoundsmentioning
confidence: 97%
“…Strategies that utilise tailor-made ligands and/or provide donor–acceptor stabilisation to M/O atoms have been applied to address the aforementioned problems and have yielded various stable compounds containing MO bonds 711. Thus, silanones (silaketones) and germanones (germaketones) with formal SiO and GeO bonds, respectively, were successfully isolated, and the variety of silanones exceeds that of the germanones 710. In addition to silanones, silicon analogues of aldehyde, ester, amide, formyl chloride, carboxylic acid, and acid anhydride compounds were also synthesised via various methods mainly by the groups of Driess, Roesky, Baceiredo, and Kato 12.…”
Section: Introductionmentioning
confidence: 99%
“…12 a Surprisingly, such analogues of germanium [LGe(O)Y] [L = a monoanionic ligand; Y = H (germaaldehyde), Cl (germaacid chloride), OR (germaester), NR 2 (germaamide), OH (germacarboxylic acid), and (OGe(O)L) germaacid anhydride] are not yet known, perhaps due to the difficulty in adding an electron-withdrawing Y atom/group to the germanium atom in light of the already heavily polarised GeO bond. Owing to our continued interest in the chemistry of germanium, we were able to isolate the Lewis acid (LA) complexes (i-Bu) 2 ATIGe(i-Pr)O → LA (LA = B(C 6 F 5 ) 3 ( IV ), ZnCl 2 ( V ), SnCl 2 ( VI ), and GeCl 2 ( VII )) of a germanone10 starting from a germanium-μ-oxo dimer [ATI = aminotroponiminate, a monoanionic bidentate ligand]. We now understand that this synthetic protocol is exploitable for the synthesis of hitherto unknown germaacid chlorides and germaesters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation